PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING - Faiz Azmi Fauzia; Junaidi Fery Efendi (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
Learning is successful can be seen from the active role of students as both input and output, and the teacher as a facilitator in improving learning outcomes. Development of learning tools is done so that learning becomes more innovative, effective, efficient and has better quality. The number of students who still have problems in understanding mathematics, because teaching material is not interesting so it is not only difficult to understand but also not serious when learning mathematics. Scrapbook learning media can make learning more interesting because it displays the appearance that students like and is memorable for students so that the learning received is longer remembered. This research will produce a product in the form of ScrapBook based problem based learning. This research is a 4-D research and development namely Define, Design, Development and Disseminate. Assessment of student effectiveness can be seen from the results of learning tests conducted on a limited test using the Problem Based Learning Scrapbook based on VIII A class Muhammadiyah Junior high school 9 Surabaya obtained 80% including with good criteria. While the results of field trials on VIII B students have a total completeness of 88% including with good criteria.